Nan Goldin’s the Ballad of Sexual Dependency - Boone, Silvana (PORTO ARTE: Revista de Artes Visuais, 2017)
This review focuses on American artist Nan Goldin’s exhibition The Ballad of Sexual Dependency, held at MoMA – The Museum of Modern Art in New York – in 2016-2017, 30 years after her first exhibition in 1986. The slideshow is a highlight with about 700 photographs produced by the artist between the 1970s and 1990s, which show the nature of the social group to which she belonged.